ANALISIS KESALAHAN PENULISAN PREPOSISI DI- DALAM KARANGAN CERITA PENDEK SISWA MA MAWAR - Rossa Cahyani Putri; Huda, Miftahul (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2024)
This research was conducted at MA Matholi’ul Anwar in the odd semester of the 2023/2024 academic year. This research aims to find out errors in writing prepositions in the short story essays of class XI.2 MA Matholi’ul Anwar students. The research method used is a qualitative descriptive method. The data in this research are three short story essays by class XI MA Matholi’ul Anwar students. The research results showed that there were 24 errors in writing the preposition di-. The error is in the form of writing a preposition that is not as it should be. The preposition di- should be separated from the next word, but in the student’s essay, all prepositions di- are written combined with the next word.